Adhesion molecules intercellular adhesion molecule-1 (ICAM-1), ICAM-3 and B7 are not expressed by epithelium in normal or inflamed colon. - Bloom, S; Simmons, D; Jewell, D (1995)
Adhesion molecules are involved in facilitating cell-mediated immune events. Because lymphocyte-epithelial cell interaction has been implicated in the pathogenesis of colonic inflammation, we analysed expression of a range of adhesion molecules on colonic epithelium in vitro and in vivo using flow cytometry, immunohistochemistry and in situ hybridization. Expression of ICAM-1 by cell lines HT29 and int407 was increased by proinflammatory cytokines interferon-gamma (IFN-gamma), tumour necrosis factor-alpha (TNF-alpha) and IL-1 but not by IL-6. Vascular cell adhesion molecule (VCAM) and E-selectin were not expressed. Immunohistochemistry using sections of inflamed colon from 16 patients with ulcerative colitis (UC), five patients with Crohn's disease (CD) and seven patients with normal colonoscopic biopsies, showed no expression of ICAM-1 on colonic epithelium. VCAM was seen in isolated lymphoid aggregates and E-selectin was expressed on endothelium. In situ hybridization showed no ICAM-1 or ICAM-3 mRNA in colonic epithelium. B7, the ligand for CD28, was not found on normal or inflamed colonic epithelium. The adhesion molecules ICAM-1, ICAM-3 and B7 are not involved in lymphocyte-epithelial cell interaction in the normal or inflamed colon. This may have implications for the development of T cell tolerance to intestinal luminal antigens.